Identification key to species of the flying lizard genus Draco Linnaeus, 1758 (Squamata: Agamidae) in Thailand - Srichairat, Nattawut; Jantrarotai, Pattanee; Duengkae, Prateep; Chuaynkern, Yodchaiy (Agriculture and Natural Resources, 2017)
A species identification key of flying lizards in the genus Draco from Thailand was constructed based on 521 preserved specimens from collections during 1967-2012 in the Natural History Museum (THNHM), National Science Museum, Technopolis, Pathum Thani, Thailand. Regardless of sexual characters, four characters were used to identify Draco spp. lizards: 1) nostril direction; 2) type of tympanum; 3) pattern of patagium; and 4) snout with or without a series of scales forming a Y-shaped figure. The specimens were identified into nine species-Draco blanfordii, Draco fimbriatus, Draco maculatus, Draco maximus, Draco melanopogon, Draco obscurus, Draco quinquefasciatus, Draco taeniopterus and Draco volans.